Boundary detection and enhancement strategy for power system bus bar stabilization-investigation under fault conditions for islanding operation - Pouryekta A.; Ramachandaramurthy V.K.; Padmanaban S.; Blaabjerg F.; Guerrero J.M. (MDPI AG, 2023)
Busbars; Distributed power generation; Electric load management; Electric power plant loads; MATLAB; Software testing; Autonomous operations; Boundary detection method; Distribution systems; Dynamic performance; Islanding; Islanding operations; Power distributions; Voltage fluctuations; Electric load shedding